Structural and immunological characterization of a biosurfactant produced by Bacillus licheniformis JF-2. - Lin, S C (1994)
Bacillus licheniformis JF-2 produces a very active biosurfactant under both aerobic and anaerobic conditions. We purified the surface-active compound to homogeneity by reverse-phase C18 high-performance liquid chromatography and showed that it is a lipopeptide with a molecular weight of 1,035. Amino acid analysis, fast atom mass and infrared spectroscopy, and, finally, 1H, 13C, and two-dimensional nuclear magnetic resonance demonstrated that the biosurfactant consists of a heterogeneous C15 fatty acid tail linked to a peptide moiety very similar to that of surfactin, a lipopeptide produced by Bacillus subtilis. Polyclonal antibodies were raised against surfactin and shown to exhibit identical reactivity towards purified JF-2 lipopeptide in competition enzyme-linked immunosorbent assays, thus providing further evidence for the structural similarity of these two compounds. Under optimal conditions, the B. licheniformis JF-2 biosurfactant exhibits a critical micelle concentration of 10 mg/liter and reduces the interfacial tension against decane to 6 x 10(-3) dyne/cm, which is one of the lowest interfacial tensions ever reported for a microbial surfactant.